MATEC Web of Conferences - Purin, M. (EDP Sciences, 2018)
Mathematical modeling of heat transfer processes proceeding together under conditions of intense phase transformations (melting and evaporation of metals) under laser action on a dimetallic target has been carried out. Based on the results of numerical simulation, it is established that the laser power exerts a significant influence on the dynamics of the melting process. It is shown that evaporation of metal in the boundary layer of the plate can also have a significant effect on the heat transfer characteristics. It is established that metal vapors forming a gas mixture in the near-wall region can absorb laser radiation and cause the phenomenon of optical resonance with increasing their critical concentration, in other words, when the metal melts, optical breakdown is possible.